Detection of Pseudomonas aeruginosa Serogroup G Using Real-Time PCR for Novel Target Genes Identified Through Comparative Genomics - Wang, Chufang; Ye, Qinghua; Ding, Yu; Zhang, Jumei; Gu, Qihui; Pang, Rui; Zhao, Hui; Wang, Juan; Wu, Qingping (Frontiers in Microbiology, 2022)
ABSTRACT Accurate serotyping is essential for effective infection control. Pseudomonas aeruginosa（P. aeruginosa） serogroup G is one of the most common serogroups found in water. Conventional serotyping methods are not standardized and have several shortcomings. Therefore, a robust method for rapidly identifying P. aeruginosa serotypes is required. This study established a real-time PCR method for identifying P. aeruginosa serogroup G strains using novel target gene primers based on comparative genomic analysis. A total of 343 genome sequences, including 16 P. aeruginosa serogroups and 67 other species, were analyzed. Target genes identified were amplified using real-time PCR for detecting P. aeruginosa serogroup G strains. Eight serogroup G genes, MMK2018_01213, MMK2018_02856, MMK2018_02857, MMK2018_02860, MMK2018_02863, MMK2018_03343, MMK2018_02686 and MMK2018_04732, were analyzed to determine specific targets. A real-time fluorescence quantitative PCR method, based on the novel target MMK2018_01213, was established to detect and identify serogroup G strains. The specificity of this method was confirmed using P. aeruginosa serogroups and non-P. aeruginosa species. The sensitivity of this real-time PCR method was 4×102 CFU/mL, and it could differentiate and detect P. aeruginosa serogroup G in the range of 4.0×103 – 4.0×108 CFU/mL in artificially contaminated drinking water samples without enrichment. The sensitivity of these detection limits was higher by 1–3 folds compared to that of the previously reported PCR methods. In addition, the G serum group was accurately detected using this real-time PCR method without interference by high concentrations of artificially contaminated serum groups F and D. These results indicate that this method has high sensitivity and accuracy and is promising for identifying and rapidly detecting P. aeruginosa serogroup G in water samples. Moreover, this research will contribute to the development of effective vaccines and therapies for infections caused by multidrug-resistant P. aeruginosa.